Anti-Mainstream Culinary: The Influence of Post-Modernism on Gastronomy in Indonesian Restaurants - Widari, Tika; Aliffiati, Aliffiati; Rahman, Luthfi Riyadh; Indra, Muhammad (IAS Journal of Localities, 2024)
The culinary movement is currently undergoing interesting developments: initially, food was a basic requirement for energy and the food consumed was usually processed from nature. Consequently, processed food often characterized the identity of specific tribes, cultures, and regions. In the modern era, food has a long history (for example, the French Revolution), with ethics and rules. This shows that modern food culture is structured and even classifies social classes. Originally, food in the modern era had a concept adapted from the serving of food in palaces, with order and layout. However, this modern presentation of food was rejected by cooks who served food in different ways. For example, enjoying meals at a high altitude and serving food with unusual artistry. With this resistance to the European-style presentation of many luxury restaurants in Indonesia, this post-modernist restaurant can attract customers. This research uses a descriptive qualitative approach. Data collection technique is conducted through visual observation via social media. The findings reveal that the flow of post-modernism and post-structuralism has influenced the way food is served in several Indonesian restaurants. The full results and discussion are presented herein.